PsSAK1, a Stress-Activated MAP Kinase of Phytophthora sojae, Is Required for Zoospore Viability and Infection of Soybean - Aining Li; Yonglin Wang; Kai Tao; Suomeng Dong; Qian Huang; Tingting Dai; Xiaobo Zheng; Yuanchao Wang (Molecular Plant-Microbe Interactions, 2010)
Mitogen-activated protein kinase (MAPK) pathways are universal and evolutionarily conserved signal transduction modules in all eukaryotic cells. In this study, PsSAK1, which encodes a stress-activated MAPK of Phytophthora sojae, was identified. PsSAK1 is highly conserved in oomycetes, and it represents a novel group of MAPK due to its pleckstrin homology domain. Reverse-transcription polymerase chain reaction analysis showed that PsSAK1 expression was upregulated in zoospores and cysts and during early infection. In addition, its expression was induced by osmotic and oxidative stress mediated by NaCl and H2O2, respectively. To elucidate the function, the expression of PsSAK1 was silenced using stable transformation of P. sojae. The silencing of PsSAK1 did not impair hyphal growth, sporulation, or oospore production but severely hindered zoospore development, in that the silenced strains showed quicker encystment and a lower germination ratio than the wild type. PsSAK1-silenced mutants produced much longer germ tubes and could not colonize either wounded or unwounded soybean leaves. Our results indicate that PsSAK1 is an important regulator of zoospore development and pathogenicity in P. sojae.